CORPORATE SOCIAL RESPONSIBILITY AND HUMAN SECURITY: AN EVALUATION OF SHELL'S CSR INITIATIVES IN CONFLICT-AFFECTED COMMUNITIES OF RIVERS STATE - ADIELE OBIANUJU PRISCA; SAM INALEGWU OGOH (International Studies Journal)
This study evaluates the impact of Corporate Social Responsibility (CSR) initiatives on human security in conflict-affected communities of Rivers State, Nigeria. The study integrates quantitative surveys and qualitative interviews to assess whether CSR interventions by Shell effectively mitigate environmental degradation, economic insecurity, and social instability. This study anchored in human security theory, which emphasizes a people-centered approach to security, the study interrogates CSR’s role beyond community development projects to its impact on economic empowerment, environmental sustainability, and conflict resolution. The findings reveal that while Shell’s CSR programs provide infrastructure, education, and healthcare, they fail to address core human security concerns. Weak stakeholder engagement and governance structures limit transparency and community participation, leading to elite capture of CSR benefits. Additionally, environmental degradation persists despite Shell’s sustainability commitments, and CSR-based economic empowerment programs remain unsustainable, failing to curb youth unemployment and militancy. The study recommends restructuring CSR interventions to incorporate holistic human security strategies and strengthening regulatory frameworks to enforce corporate accountability. This research contributes to the literature by shifting the focus from corporate philanthropy to structural governance solutions. Unlike previous studies that document CSR activities, this study critically examines their effectiveness in promoting human security and highlights the need for policy-driven CSR reforms to achieve sustainable peace and development in oil-producing regions.